Bioactive Polymeric Nanoparticles of Moringa oleifera Induced Phyto-Photothermal Sensitization for the Enhanced Therapy of Retinoblastoma - Sushma Venkata Mudigunda; Deepak B. Pemmaraju; Sri Amruthaa Sankaranarayanan; Aravind Kumar Rengan (MDPI AG, 2023)
Treatment of retinoblastoma is limited due to its delayed detection and inaccesbility of drugs to reach the retina crossing the blood-retinal barrier. With the advancements in nanotechnology, photothermal therapy (PTT) employing plasmonic nanomaterials and/or NIR dyes have emerged as an affordable alternative owing to the spatial control that is offered by the modality leading to localized and enhanced therapeutic efficacy with minimal invasiveness. However, the modality is limited in its clinical application owing to the increased heat shock resistance of the tumor cells in response to the heat that is generated via PTT. Hence, in this study, we explore the role of novel biomolecular fraction of Moringa oleifera (DFM) encapsulated within a polymeric nanosystem, for its anti-heat shock protein (HSP) activity. The MO extract was co-encapsulated with NIR sensitizing dye, IR820 into a biodegradable polycaprolactone (PCL) nano-delivery system (PMIR NPs). The photothermal transduction efficacy of PMIR NPs was validated in vitro against retinoblastoma cell lines. The inherent fluorescence of DFM was utilized to evaluate the cellular internalization of the PMIR NPs using fluorescence microscopy and flow cytometry. The overall oxidative protein damage and downregulation of HSP70 expression upon treatment with PMIR NPs and NIR laser irradiation was evaluated using densiometric protein analysis and Western blotting. Overall, the PMIR NPs exhibited excellent anti-cancer activity when combined with PTT with downregulated HSP70 expression against retinoblastoma cells.